Impact of Out-of-School STEM Activities on STEM Career Choices of Female Students - Donmez, Ismail (Ani Yayincilik, 2021)
Purpose: The aim of this research was to analyze change of STEM career choices of female students having different cognitive styles who participated in out-of-school STEM activities. Socio-economically disadvantaged, high academic achiever 20 female students participated in the research. Participants received integrated STEM training for six days and met STEM professionals working in universities and technoparks. Research Methods: The embedded integrated pattern, one of the mixed research methods, was used in the research. Quantitative data consisted of STEM career interest scale, Witkin's hidden figures test and Holland occupational inventory. Interview form was used as qualitative data. Findings: The results of the study showed that the implementation of out-of-school STEM activities contributed to an increase of STEM career interest. It was seen that there was a significant increase in STEM career interests of the independent participants. Field independent students were more interested in STEM fields. After STEM-related activities, 60% of the participants changed their occupational preferences towards STEM fields. STEM role models were found to support students' thinking about their careers and goal development. Implications for Research and Practice: Implementing out of school STEM activities and meeting with STEM professionals will contribute to students' career choice in STEM fields. Understanding the cognitive styles of students will contribute to identifying STEM career interests. (C) 2021 Ani Publishing Ltd. All rights reserved
DONMEZ, Ismail/0000-0002-7792-0169
Keywords: Cognitive styles; female students; out-of-school; STEM; STEM career development